[Memo from Jack Shoemaker to Hurst Marshall regarding League of Latin American Citizens] - JACK SHOEMAKER (Tufts Archival Research Center, 2007)
Memo from Jack Shoemaker to Hurst Marshall regarding the League of Latin American Citizens (LULAC). Describes efforts to get in touch with LULAC's Southeastern office. Discusses conversation with Robert Canino requesting support in the fight against cigarette taxes. Asks for advice as to how to tactfully explain why Hispanics should get involved and how they would benefit.